Analysis of conjecture ability from the perspective of learning styles - Robisha Zarifa Ribaah; Ahmad Sofi Yullah; Marsida Aulia Rahma (Universitas Sarjanawiyata Tamansiswa, 2025)
This study investigates students' ability to make conjectures based on their preferred learning styles. A qualitative descriptive research methodology was applied. The participants consisted of ten mathematics majors enrolled in the 2024–2025 academic year. Researchers employed a purposive sampling strategy to select the subjects. The test questions and learning style surveys used in the assessment tool were reviewed and approved by expert educators. Data from the test and the learning style questionnaire were analyzed to determine students' learning styles and their ability to formulate conjectures. The results indicate that visual learners demonstrated the highest ability to make conjectures, as they tend to perceive mathematical concepts visually before solving problems. In contrast, students with auditory or kinesthetic learning styles exhibited lower conjecture-making abilities, primarily due to memory-related challenges. However, students with these learning styles can still improve their conjecture skills with appropriate instructional approaches. Enhancing students' ability to formulate conjectures enables them to better explain mathematical concepts, derive information from mathematical problems, anticipate outcomes, develop solutions, and construct well-founded arguments. This study contributes to the field of mathematics education by providing insights into how different learning styles influence students' conjecture-making abilities, which can inform the development of more effective teaching strategies.